The chief learning officer: A model role for integrating HR and strategic planning functions in libraries. Issue 6 (15th August 2017) - Farrell, Robert
Abstract : Purpose: The purpose of this paper is to put forward the position of chief learning officer (CLO) as a potential new role or models for new roles in libraries wishing to integrate human resources, strategic planning, and budgeting. Design/methodology/approach: The paper reviews the history and present functions of the CLO role in the corporate world, correlating work within the library field with key aspects of the position as way by which to conceptualize the integration of disparate library operations. Findings: The position of CLO has not yet entered the library and information science (LIS) discourse. Practical implications: Libraries that do not have CLO-like positions in their organizations may benefit from adopting or adapting the position to their libraries. Originality/value: The paper introduces the CLO position to the field of LIS.